Formation of Arithmetic Musical Competence in Students - Oshanova, Nurzhamal T.; Shekerbekova, Shirinkyz T.; Sagimbaeva, Ainur E.; Arynova, Gylnar C.; Kazhiakparova, Zhadyra S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of this study is to form the arithmetic musical competency of students on the basis of Al-Farabi’s theoretical musical heritage. In this context, the work “The Great Book of Music” is of great importance. In this work, he gives not only a scientific explanation of the origin of sounds as properties of matter but also gives an idea of the arithmetic principles of the emergence of harmony and musical melodies. Background: Musical competence is described as an ability and an aptitude to adequately perceive and emotionally respond (react) to music, to transfer musical perception into the ability to think using artistic images. In school, its formation occurs during the study of a discipline "Music", among special subject competencies that form within this subject an arithmetic musical competence can be distinguished. Method: Judging from the musical theory composition method, Al-Farabi suggests an innovative method to improve the musical development of students with intellectual disabilities which consists of the individual preparation of a training plan. Results: As a result of this study, it was determined that the problem of the formation of arithmetic musical competence in the learning process is relatively new and insufficiently studied. Arithmetic musical competence can be formed on the basis of teaching the method of the musical theory of composition Al-Farabi. Conclusion: The experiment results allows for the conclusion about the advantages of the formation of musical competence of students via knowledge of music theory.